Optimum time management of first pre-flight departure by LCC operators at KLIA2 / Saanthi Pohmalay - Saanthi , Pohmalay (2019)
The aim of the research was to investigate, the management of first flight, delay in first flight take off due to practices of matching pilots and aircraft on Low Cost Carriers (LCC). A case study and field study research strategies were employed for the methodology. A sample of 61 first flights of the day for LCC to various destination departing from KLIA2 over a period of one month was used for quantitative analysis. The qualitative aspect was undertaken through interviews of focus groups (pilots, passengers and customer service representatives). A summary and significance test were undertaken to analyze the data for patterns and significance of delays. The research findings indicate there was significant delays in first flight take-off during the study period. Some of these delays were identified to the current system of pilots and aircraft matching. A tentative solution in the form of best practices was suggested for effective management of the first flight by LCC operators. From a theoretical point of view, it expounds and adds on to the understanding of delay, especially the first flights of the day and especially for LCC operators. There are a few limitations in the study as the focus is only on the first flight management; especially the match between aircraft and pilots for a timely departure. Other factors could also play a significant part; both controllable and uncontrollable. A comprehensive study on it can identify significance and the significance of the overall delay. An area not covered by this study and a potential cause for a separate study is interviews with top management staff; this could confirm the existence of the problem for a broader understanding of the issue and its relationship to management and cost-effective productivity.